Myeloid Kdm6b deficiency results in advanced atherosclerosis. (August 2018) - Neele, Annette E.; Gijbels, Marion J.J.; van der Velden, Saskia; Hoeksema, Marten A.; Boshuizen, Marieke C.S.; Prange, Koen H.M.; Chen, Hung-Jen; Van den Bossche, Jan; van Roomen, Cindy P.P.A.; Shami, Annelie; Levels, Johannes H.M.; Kroon, Jeffrey; et al.
Abstract: Background and aims: Atherosclerosis is a lipid-driven chronic inflammatory disorder of the arteries, and monocytes and macrophages play a central role in this process. Within the atherosclerotic lesion, macrophages can scavenge modified lipids and become the so-called foam cells. We previously reported that the epigenetic enzyme Kdm6b (also known as Jmjd3) controls the pro-fibrotic transcriptional profile of peritoneal foam cells. Given the importance of these cells in atherosclerosis, we now studied the effect of myeloid Kdm6b on disease progression. Methods: Bone marrow of myeloid Kdm6b deficient ( Kdm6b del ) mice or wild type littermates ( Kdm6b wt ) was transplanted to lethally irradiated Ldlr −/− mice fed a high fat diet for 9 weeks to induce atherosclerosis. Results: Lesion size was similar in Kdm6b wt and Kdm6b del transplanted mice. However, lesions of Kdm6b del mice contained more collagen and were more necrotic. Pathway analysis on peritoneal foam cells showed that the pathway involved in leukocyte chemotaxis was most significantly upregulated. Although macrophage and neutrophil content was similar after 9 weeks of high fat diet feeding, the relative increase in collagen content and necrosis revealed that atherosclerotic lesions in Kdm6b del mice progress faster. Conclusion: Myeloid Kdm6b deficiency results in more advanced atherosclerosis. Highlights: Collagen content is enhanced in atherosclerotic lesions of Kdm6b deficient mice. Necrosis is enhanced in atherosclerotic lesions of Kdm6b deficient mice. Myeloid Kdm6b deficiency results in advanced atherosclerosis.